Prevalence and correlation with sex, age, and dental status of bone apposition at the mandibular angle and radiographic alterations of the temporomandibular joints: a retrospective observational study in an adult Swiss population - Michelle Simonek; Jens Christoph Türp; Michael M. Bornstein; Dorothea Dagassan-Berndt (BMC, 2024)
Abstract Background The purpose of this study was to determine the prevalence of radiographic changes in the mandibular angle (bone apposition) and osseous alterations in the temporomandibular joints (TMJs) in the adult population of Switzerland. In addition, the study intended to investigate possible correlations between the two sites of contour bone changes (mandibular angle and TMJ) and to analyze various patient-related factors, including sex, age, dental status, and medical history. Methods Panoramic radiographs of 600 patients distributed into six age groups (283 females, 317 males, aged 20 to 79 years) were included to evaluate radiographic changes. The bone in the mandibular angle region and the shape of the condylar heads were examined for contour changes (bone apposition at the jaw angles and osseous changes of the TMJs). General estimating equations, binormal tests, and chi-squared tests were used for statistical analysis. Results Approximately half of the mandibular angles (47.8%) showed bone apposition, mostly bilateral. TMJ alterations were less common (27%), often unilateral, with flattening being the most frequent finding. No significant correlation was found between the two sites. Bone apposition at the mandibular angle showed a significant male predominance, whereas TMJ changes did not differ by sex. Alterations in both sites increased with age, and were not related to dental status or analgesic use. Conclusions Bone apposition at the mandibular angle should be interpreted as part of the natural functional adaptation of the bone associated with aging. Assuming that parafunctional habits may influence the development and progression of alterations in the mandibular angle or TMJs, the presence of radiographic changes in these areas should prompt dental clinicians to investigate further in this direction. Trial registration The study was approved by the Swiss Association of Research Ethics Committees (swissethics), BASEC reference number: 2020-00963 (25.05.2020).